A Frustrated and Confused Lewis Pair. (13th October 2016) - McQuilken, Alison C.; Dao, Quang Minh; Cardenas, Allan Jay P.; Bertke, Jeffery A.; Grimme, Stefan; Warren, Timothy H.
Abstract: We report a new class of frustrated Lewis pairs (FLPs) by the hydroboration of bulky isocyanates iPr2 ArNCO ( iPr2 Ar=2, 6‐ i Pr2 C6 H3 ) and Ph2tBu ArNCO ( Ph2tBu Ar=2, 6‐Ph2 ‐4‐ t BuC6 H2 ) with Piers' borane (HB(C6 F5 )2 ). While hydroboration of smaller isocyanates such as iPr2 ArNCO leads to isocyanate—N/B FLP adducts, hydroboration of the bulkier Ph2tBu ArNCO allows isolation of the substrate‐free aminoborane with a short, covalent N−B bond. This confused FLP reversibly binds unsaturated substrates such as isocyanates and isocyanides, suggesting the intermediacy of a "normal" FLP along the reaction pathway, supported by high‐level DFT studies and variable‐temperature NMR spectroscopy. These results underscore the possibility of FLP behavior in systems that possess no obvious frustrated Lewis acid–base interaction.